Physicians' perspectives on irritable bowel syndrome, diagnosis and management in India: insights from in-clinic questionnaire-based survey study with a focus on Rifaximin - Borkar, Nilesh; Gote, Sonali; Salvi, Pradnya; Khobragade, Kunal (International Journal Of Community Medicine And Public Health, 2025)
Background: In India, irritable bowel syndrome (IBS) contributes notably to patients’ discomfort and places a considerable strain on healthcare resources. With Physicians as a primary care provider for IBS patients, this survey objective was to explore their practices, perspectives and experience with Rifaximin in management of IBS with Rifaximin in the management of IBS-D. Methods: A cross-sectional structured electronic survey consisting of 20 multiple-choice questions was administered to 302 physicians across India. Results: A total of 302 physicians participated in the survey, reporting diverse monthly caseloads of patients diagnosed with IBS. Among them, 32.81% managed between 10–20 patients per month. IBS with diarrhea (IBS-D) emerged as the most commonly encountered sub-type. Rifaximin was identified as a frequently prescribed therapy for IBS-D, with physicians’ observance in reduction of 40-80% pain (47.07% patients), bloating (50.20%), diarrhea (47.83%) and symptom urgency (47.08%), with preferred dose of 400 mg twice daily (44.66%). Conclusions: IBS remains one of the most frequently encountered functional gastrointestinal disorders among Physicians, with clinical judgment as primary diagnosis. Rifaximin was commonly preferred for managing IBS-D due to its proven efficacy, minimal systemic absorption, and strong safety profile.